Acousto-optic gyrotropic-crystal-based modulator with a rotating polarisation vector. (March 2017) - Kotov, V.M.; Averin, S.V.; Kotov, E.V.; Voronko, A.I.; Tikhomirov, S.A.
Abstract: We study the influence of ellipticity of gyrotropic-crystal eigenwaves on the output characteristics of an acousto-optic (AO) modulator based on the interferometer scheme. The schemes of AO modulators are considered, which provide the polarisation vector rotation frequency fn /2, where f is the frequency of the acoustic wave, and n is the integer. Preference is given to the scheme combining cascade and polarisation-independent diffraction. An experimental layout of the AO modulator operating at f = 44.5 MHz is described, the modulation frequency of the output laser light intensity being 89 MHz. The frequency of the electrical signal from the photodetector is equal to 179.5 MHz.